Probing the Chemical Structure in Diamond-Based Materials Using Combined Low-Loss and Core-Loss Electron Energy-Loss spectroscopy. (25th March 2014) - Longo, Paolo; Twesten, Ray D.; Olivier, Jaco
Abstract We report the analysis of the changes in local carbon structure and chemistry caused by the self-implantation of carbon into diamond via electron energy-loss spectroscopy (EELS) plasmon energy shifts and core-edge fine structure fingerprinting. These two very different EELS energy and intensity ranges of the spectrum can be acquired under identical experimental conditions and nearly simultaneously using specially designed deflectors and energy offset devices known as "DualEELS." In this way, it is possible to take full advantage of the unique and complementary information that is present in the low- and core-loss regions of the EELS spectrum. We find that self-implanted carbon under the implantation conditions used for the material investigated in this paper creates an amorphous region with significant sp2 content that varies across the interface.